The Role Of Professional Competence In The Training Of Reserve And Reserve Officers - Hamroev Bakhriddin Jumakovich (Euro Asian Journal Publishing, 2025)
The article discusses the role of professional competence in the training of reserve and reserve officers
Keywords: competence; professional training; military education